Middle leaders and managers’ perspectives of distributive leadership during COVID-19 - Fourie, Laurette; Naidoo, Parvathy (Perspectives in education, 2022)
On a global level, COVID-19 has shaken the foundations of every sector. In the South African education context, the traditional methods of teaching, learning, and managing schools changed drastically overnight and management roles and responsibilities were pushed to unprecedented levels. Moreover, the roles of middle leaders and managers took place within a more distributive framework, encouraging school leaders to adopt varying styles of leadership to cope with the demands of COVID-19. For this study, middle leaders constitute departmental heads, grade heads and subject heads. This study utilised a qualitative research design, adopting a case study approach within the interpretivist paradigm. Three departmental heads and seven post level one educators who occupy grade heads/leaders’ roles in a primary school constituted the sample. Semi-structured individual interviews were conducted with participants to gain their understanding of how distributive leadership was practiced during the pandemic. Four themes emerged, namely leadership styles and factors informing the leadership behaviour and leadership growth of middle leaders and managers in schools; middle leaders’ and managers’ perceptions of distributive leadership and the responsibilities of the different stakeholders; the impact of COVID-19 on distributive leadership as perceived by middle leaders and managers; and the advantages and disadvantages of distributive leadership practices. The study recommends that School Management Teams (SMTs) involve middle leaders and managers to a greater degree to secure an effective ‘buy-in’ to the concept of distributive leadership and that middle managers offer opportunities for others to lead, by developing leadership-specific courses for them. SMTs must also ensure that individuals have a stable working environment where their psychological, sociological, and emotional needs are respected, fulfilled, and validated during any pandemic.